2020
DOI: 10.3390/antiox9090889
|View full text |Cite
|
Sign up to set email alerts
|

Rats Genetically Selected for High Aerobic Exercise Capacity Have Elevated Plasma Bilirubin by Upregulation of Hepatic Biliverdin Reductase-A (BVRA) and Suppression of UGT1A1

Abstract: Exercise in humans and animals increases plasma bilirubin levels, but the mechanism by which this occurs is unknown. In the present study, we utilized rats genetically selected for high capacity running (HCR) and low capacity running (LCR) to determine pathways in the liver that aerobic exercise modifies to control plasma bilirubin. The HCR rats, compared to the LCR, exhibited significantly higher levels of plasma bilirubin and the hepatic enzyme that produces it, biliverdin reductase-A (BVRA). The HCR also ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…We had previously shown that mice with the Gilbert's mutation UGT1A1*28 and hyperbilirubinemia were resistant to high-fat diet-induced hepatic steatosis by inhibiting de novo lipogenesis and activation of β-oxidation (Hinds et al, 2017). We have also shown that exercise elevated plasma bilirubin by suppressing hepatic UGT1A1 and increasing biliverdin reductase-A (BVRA) (Hinds et al, 2020), the enzyme that generates bilirubin (Adeosun et al, 2018;O'Brien et al, 2015), which improved hepatic glycogen storage and PPARα target genes (Hinds et al, 2020). Here, we found that PEG-BR reduced SCD1 and FAS while activating PPARα and ACOX1, improving hepatic steatosis in obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…We had previously shown that mice with the Gilbert's mutation UGT1A1*28 and hyperbilirubinemia were resistant to high-fat diet-induced hepatic steatosis by inhibiting de novo lipogenesis and activation of β-oxidation (Hinds et al, 2017). We have also shown that exercise elevated plasma bilirubin by suppressing hepatic UGT1A1 and increasing biliverdin reductase-A (BVRA) (Hinds et al, 2020), the enzyme that generates bilirubin (Adeosun et al, 2018;O'Brien et al, 2015), which improved hepatic glycogen storage and PPARα target genes (Hinds et al, 2020). Here, we found that PEG-BR reduced SCD1 and FAS while activating PPARα and ACOX1, improving hepatic steatosis in obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…These imply that possibly inducing heme oxygenase or BVRA might improve adiposity by increasing plasma bilirubin [ 35 ]. This concept is supported in a study showing that high-aerobic-capacity running rats had significantly higher plasma bilirubin and increased hepatic BVRA and PPARα than the low-running-capacity obese animals [ 36 ].…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, intensive regular exercise, as seen in athletes, is correlated with elevated concentrations of total bilirubin [ 115 ]. Animal experiments showed that exercise stimulates pathways that raise serum bilirubin levels through alterations in the levels of hepatic enzymes; namely, increasing the expression of biliverdin reductase and consequently increasing bilirubin synthesis, as well as decreasing the expression of UGT1A1, which converts the biologically active unconjugated bilirubin into the non-active conjugated form [ 116 ].…”
Section: Potential Interventions To Modulate Serum Bilirubin Levels In Obesitymentioning
confidence: 99%